Switch of the magnetic field effect on photon upconversion based on sensitized triplet–triplet annihilation. Issue 12 (11th November 2016) - Yonemura, Hiroaki; Naka, Yuji; Nishino, Mitsuhiko; Sakaguchi, Hiroshi; Yamada, Sunao
Abstract : Positive magnetic field effects on photon upconversion based on sensitized triplet–triplet annihilation are observed for the first time. Abstract : Magnetic field effects (MFEs) on photon upconversion based on sensitized triplet–triplet annihilation (TTA-UC) are examined in platinum(ii ) octaethylporphyrin/9, 10-diphenylanthracene (DPA) systems at different DPA concentrations and laser power densities. Positive MFEs on TTA-UC are observed for the first time and are most likely attributable to aggregation of DPA.